Dose routine intraoperative Double J stent insertion avoid urine leakage after open partial nephrectomy? - Bosnali, Efe; Dillioglugil, Ozdal; Teke, Kerem; Yilmaz, Hasan; Bayrak, Busra Yaprak; Uslubas, Ali Kemal; Avci, Ibrahim Erkut; Argun, Omer Burak; Kara, Onder (PAGEPRESS PUBL, 2022)
Objective: To evaluate the impact of Double stent (DJS) insertion during open partial nephrectomy (OPN) on postoperative prolonged urinary leakage. Materials and methods: A retrospective study was made in consecutive cases of OPN performed between 2002 and 2020 for localized kidney tumors at our tertiary center. Urinary leakage was defined as drainage > 72 hours after surgery by biochemical analysis consistent with urine or radiographic evidence of urine leakage. The patients were divided into two groups according to intraoperative DJS placement, and compared regarding clinicopathologic characteristics, perioperative and postoperative outcomes. Univariate and multivariate logistic regression analyses were performed to determine the factors associated with urinary leakage after the operation. Results: Review of records identified 182 patients who were included in the study. In 73 (40\%) patients PN was performed without insertion of a DJS. Thus, 109 (60\%) of patients had a DJS inserted. Apart from higher preoperative eGFR values among patients with DJS (96.6 vs. 94.3 mL/min/1.73 m(2)

p = 0.03), demographic characteristics were similar between groups. The two groups were not different regarding perioperative, postoperative and clinicopathologic outcomes. Patients with DJS had longer ischemia times (31 vs. 23 min

p = 0.02) and longer length of stay (6 vs. 5 days

p = 0.04). Urinary leakage was seen in 7.6\% (n = 14) of all patients and it did not differ according to DJS placement (DJS+ 9.2 vs. DJS- 5.5\%

p = 0.41). On multivariate analysis, the tumor nearness to the collecting system was the sole independently significant factor (p = 0.04) predicting postoperative urine leak. Conclusions: Routine intraoperative DJS insertion during OPN does not appear to reduce the probability of postoperative urine leak.
Keywords: Kidney tumor; Double J stent; Urine leakage; Partial nephrectomy